Exploring the phonetic sources of the North Korean dialect accent produced by North Korean refugees in Seoul - Jung, Hwanmin; Oh, Jeahyuk; Han, Jeong-Im (Frontiers in Language Sciences, 2025)
This study explored the acoustic characteristics of second-dialect speech that give rise to its accent perception. Specifically, North Korean (NK) dialect speech samples were collected from NK refugees in Seoul, South Korea. The simple sentences to evaluate potential phonetic predictors of NK accent were constructed and then six of them to test the vowel contrasts of /o-ʌ/ and /u-∔/, acoustic cues for stops, place cues for affricates, and intonation features were selected by trained phoneticians. Forty-nine native Korean speakers of the Seoul South Korean (SK) dialect rated the accentedness of the sentences produced by 34 NK participants. The results of the accent ratings as well as the acoustic measurements revealed that the contrast of the vowel pair /o-ʌ/, which had the opposite spectral relationship to that in the SK dialect, played the most important role in robustly predicting NK dialect accent. The contrast between lenis and aspirated stops showed its lowest rating, and NK speakers used both Voice Onset Time (for NK) and F0 (for SK) cues. The current results contribute to second-dialect acquisition by providing invaluable empirical data from NK refugees, which are still underexplored in this field.